Implementation of a Multidisciplinary Expert Testicular Cancer Tumor Board Across a Large Integrated Healthcare Delivery System Via Early Case Ascertainment. (2021) - Harzstark, Andrea L.; Altschuler, Andrea; Amsden, Laura B.; Alavi, Mubarika; Liu, Liyan; Presti, Joseph C.; Brenman, Leslie Manace; Walker, Lauren C.; Ryken, Rene R.; De Mucha Flores, Aileen C.; Nichols, Craig; Herrinton, Lisa J.
Abstract : PURPOSE: In 2016, Kaiser Permanente Northern California began regionalizing testicular cancer care using population-based tumor board review. This mixed methods evaluation describes implementation outcomes and learnings. METHODS: We conducted in-depth interviews with key stakeholders, administered surveys to local oncologists and urologists, and used clinical data to evaluate changes in care delivery during 2015-2018. RESULTS: An average of 135 patients with testicular cancer were diagnosed each year. Interviews with 16 key stakeholders provided several insights. Implementation resulted in high levels of satisfaction, was dependent on leadership and staff at various levels, and required technology and consulting solutions aligned to user agreements and clinical workflows. Of 123 local oncologists and urologists who completed surveys, 97% understood why care was regionalized and 89% agreed that tumor board review improved treatment decisions. Among 177 patients with stage I seminoma, the percentage appropriately observed rather than treated with adjuvant chemotherapy or radiation therapy increased from 48% (95% CI, 35 to 62) in 2015 to 87% (75 to 99) in 2018. Review altered care based on pathology and radiology re-review in 14.5 % of cases. CONCLUSION: Regionalization was feasible and effective.